The Influence of Affective Commitment and Workload on Turnover Intention at PT Mega Artha Lintas Data - Nugroho Adi Wibowo; Fandi Fatoni (Lavish Opulent Education, 2025)
This research examines the turnover intention at PT Mega Artha Lintas Data by analyzing the impact of affective commitment and workload. The subjects of this research were employees of PT Mega Artha Lintas Data, with a total of 45 respondents obtained through an online questionnaire. This is a quantitative study using multiple linear regression analysis with the assistance of SPSS version 25 for Windows. It was found that affective commitment does not have a significant effect on turnover intention. Similarly, workload also does not significantly affect employees' turnover intention. These findings imply that PT Mega Artha Lintas Data should consider other factors beyond the two variables studied to reduce employees’ intention to leave the company. For future research, it is recommended to explore additional predictors of turnover intention such as compensation, job satisfaction, and leadership style, and to consider qualitative methods to uncover underlying motivations.